Die geheim van die prediking: om mondig te word - J. Cilliers (Acta Theologica)
This article contends that preaching is a speech-act in which the voice of the preacher – symbol of his or her personality and spirituality - has an important role to play. It argues that the voice of the preacher is a factor not to be overlooked in the dynamic structure of communication, and should be cultivated in a theologically responsible manner. The function of the voice of the preacher should, however, not be understood as a new, homiletical moralism, but in its relationship to (a) the salvation works of God, (b) the relational integrity of the preacher, (c) the integration of prayer within the framework of the preacher's theology, and (d) a life of virtue before God. The main thrust of the argument is that preaching is constituted simultaneously by a deeply human and profoundly divine activity in the life of the church.